2016
DOI: 10.15871/1517-8595/rbpa.v18nespp517-529
|View full text |Cite
|
Sign up to set email alerts
|

Análise da Cinética de Secagem em Camada Fina do Arroz Vermelho em Casca

Abstract: Os objetivos deste trabalho foram ajustar diferentes modelos matemáticos aos dados experimentais da secagem do arroz vermelho em casca em camada fina para as temperaturas de 40, 50, 60, 70 e 80 °C na velocidade de 0,8 m s-1 e teor de água de 25% base úmida, determinar e avaliar o coeficiente de difusividade efetiva, obter a energia de ativação do processo, bem como determinar suas propriedades termodinâmicas. O ajuste dos modelos matemáticos aos dados experimentais foi realizado através de análise de regressão… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…According to Araújo et al (2017), the positive value of Gibbs free energy is characteristic of an endergonic reaction, in which it requires an addition of energy from the medium in which the product is involved for the reaction to Thus, as predicted, this study revealed consistent results regarding the behavior of the thermodynamic properties of the mathematical models used, as the drying temperature was increased. This pattern of behavior was also observed in previous studies, such as that by Sousa et al (2016), who investigated the thermodynamic properties of the drying kinetics of unhusked red rice grains at different temperatures. Furthermore, authors such as Rashid et al (2023) found a similar behavior when evaluating the drying of black rice grains at temperatures of 50, 60 and 70 ºC.…”
Section: Activation Energy and Thermodynamic Properties Of The Processsupporting
confidence: 87%
See 1 more Smart Citation
“…According to Araújo et al (2017), the positive value of Gibbs free energy is characteristic of an endergonic reaction, in which it requires an addition of energy from the medium in which the product is involved for the reaction to Thus, as predicted, this study revealed consistent results regarding the behavior of the thermodynamic properties of the mathematical models used, as the drying temperature was increased. This pattern of behavior was also observed in previous studies, such as that by Sousa et al (2016), who investigated the thermodynamic properties of the drying kinetics of unhusked red rice grains at different temperatures. Furthermore, authors such as Rashid et al (2023) found a similar behavior when evaluating the drying of black rice grains at temperatures of 50, 60 and 70 ºC.…”
Section: Activation Energy and Thermodynamic Properties Of The Processsupporting
confidence: 87%
“…As the process progresses, the drying rate decreases, demonstrating greater resistance in removing water from the product until equilibrium is reached between the product and the drying air. According to Sousa et al (2016), in this period, the internal resistance to water transport becomes greater than the external resistance, allowing water transport to occur by capillary flow, liquid diffusion or vapor diffusion. In Figure 3, we can see that the average times needed to complete the drying process of black rice were 1710, 1530, 1110, 1050 and 810 minutes, respectively, for temperatures of 35, 45, 55, 65 and 75ºC.…”
Section: Drying Kinetics Of Black Rice Grains In Thin Layermentioning
confidence: 99%
“…For both samples, there were gradual reductions in the variation in enthalpy (4H), inversely proportional to the increase in temperature; and the positive nature of 4H reflected an endothermic transformation with heat absorption, a behavior related to the increase in partial pressure of the water vapor in the material caused by the increase in drying air temperature. Thus, there is an increase in the rate of water diffusion from the inside to the surface of the material, leading to a loss of water from the product by desorption (Araújo et al, 2017;Sousa, Cavalcanti-Mata, Duarte, Almeida, & Rosa, 2016). T A B L E 5 Parameters of the mathematical models fitted to the drying data of the residual trapi a seeds, plus the coefficients of determination (R 2 ), MSD, and chi-square (χ 2 ) values The values for the variation in enthalpy were shown to be lower for the residual peel, indicating that less energy was required for the drying process to occur, and that at higher temperatures, less energy would be required for drying (Corrêa, Oliveira, Oliveira, Botelho, & Goneli, 2017).…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%
“…Ao analisar a Tabela 6, observa-se que ocorre a diminuição da entalpia (ΔH) com o aumento da temperatura do ar de secagem para todos os modelos analisados. Em concordância com Sousa (2017) esse comportamento está interligado ao aumento da pressão parcial de vapor de água no material com o aumento da temperatura, desta forma, ocorre o aumento da velocidade de difusão da água do interior para a superfície do grão, ocorrendo perda da água do produto por dessorção. Assim, este estudo correspondeu as expectativas, pois apresentou menores valores de entalpia em temperaturas de secagem mais elevadas, indicando que menos energia é necessária para remover a água ligada ao produto durante a secagem em temperaturas mais altas.…”
Section: Modelosunclassified